Упростите выражение 1/√3+2 + 13/4+√3 - 11/1-2√3

timaglushko200 timaglushko200    3   03.12.2020 05:55    5

Ответы
LaMihaLa LaMihaLa  02.01.2021 05:56

Объяснение:

\frac{1}{\sqrt{3}+2 } +\frac{13}{4+\sqrt{3} } -\frac{11}{1-2\sqrt{3} } =\frac{1}{2+\sqrt{3} } +\frac{13}{4+\sqrt{3} }+\frac{11}{2\sqrt{3}-1 } =\\=\frac{2-\sqrt{3} }{(2+\sqrt{3})*(2-\sqrt{3}) }+\frac{13*(4-\sqrt{3}) }{(4+\sqrt{3})*(4-\sqrt{3}) } +\frac{11*(2\sqrt{3}+1) }{(2\sqrt{3} +1)*(2\sqrt{3}-1) }=\\

=\frac{2-\sqrt{3} }{2^2-(\sqrt{3})^2 }+\frac{13*(4-\sqrt{3}) }{4^2-(\sqrt{3})^2} }+\frac{11*(2\sqrt{3}+1) }{(2\sqrt{3})^2-1^2 }=\frac{2-\sqrt{3} }{4-3} +\frac{13*(4-\sqrt{3}) }{16-3}+\frac{11*(2\sqrt{3} +1)}{12-1}=\\=\frac{2-\sqrt{3} }{1} +\frac{13*(4-\sqrt{3}) }{13}+\frac{11*(2\sqrt{3} +1)}{11}= 2-\sqrt{3}+4-\sqrt{3}+2\sqrt{3}+1=7.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра